OPINION OF FRESH MEDICAL GRADUATES ABOUT PLASTIC AND RECONSTRUCTIVE SURGERY AS THEIR CHOICE OF SPECIALTY - Suraya, Faryal; Hassnain, Jamal Uddin Majoob; Sadaf, Nazia; Othman, Haila; Munshi, Nada Mohammed (Journal of Postgraduate Medical Institute, 2016)
Objectives: This study was conducted to determine the approach of recent medical graduate towards adopting PRS as their choice of specialty, and to have a direct assessment of their PRS perception. Methodology: After, ethical board approval, and consent, medical gradu -ates of the years 2011 to 2013, from King Saud University and couple of oth-er centers, in Riyadh, KSA, were invited to participate in the survey through questionnaires. Results: A total number of 150 questionnaires were included in the final anal -yses. More than 95% of respondents were interested in post graduation with mean age of 25.95 years, most of them graduated in 2013. Out of total 150 respondents, 45 (31.46%) were interested in surgical related specialties, fresh medical graduates interested in Plastic and reconstructive surgery constituted 11 (7.33%) of all respondents, 11(100%) of PRS group, related their choice to personal interest, while 9 of them declared some financial incentives. Most of recent graduates perceived PRS as related to cosmetic and burn surgery, while few had understanding about its microvascular and hand surgery techniques. Conclusion: Rising popularity of PRS among general population and their awareness regarding cosmetic procedures, has introduced a new trend in career selection for medical graduates. Statistical Analysis was performed through SPSS version 21.